LEGISLATIVE TURNOVER IN THE BALTICS AFTER 1990: WHY IS IT SO HIGH AND WHAT ARE ITS IMPLICATIONS? - Kuklys, Mindaugas (Baltic Journal of Political Science, 2013)
This article discusses the causes and potential consequences of the high legislative turnover in Estonia, Latvia, and Lithuania in the period from 1990 onwards. The main findings from the subject-related literature are being confronted with the data on the Baltic parliamentary recruitment. The analysis leads to the conclusion that the path dependence (length of the previous non-democratic regime) and the supply-side volatility are the most convincing explanations for the high turnover among Baltic legislators.